A listing of CARICOM meetings arranged alphabetically by acronym/abbreviation : 1973-2006 (CCS [Georgetown]GY, 2009)
Provides a record of meetings convened by the CARICOM Secretariat during the period 1973 to 2006. Lists also, meetings which are considered to be of importanc to CARICOM..
Keywords: CONFERENCE PAPERS